Genetic and immunological characterization of G9 group A porcine rotaviruses in China. (24th May 2022) - Li, Yu; Wang, Fengxuan; Kan, Ruici; Cao, Hui; Tang, Cheng; Yue, Hua; Zhang, Bin
Abstract: G9 group A rotaviruses (RVAs) are considered emerging pathogens in pigs and humans, and pigs are considered a potential host reservoir for human G9 RVAs. In this study, RVAs of two genotypes, G9P[23] and G9P[13], were successfully isolated and the genomic sequences were obtained, the genome constellation is G9‐P[23]‐I5‐R1‐C1‐M1‐A8‐N1‐T1‐E1‐H1 and G9‐P[13]‐I5‐R1‐C1‐M1‐A8‐N1‐T7‐E1‐H1 respectively. One strain which amplified from clinic faecal sample had an unique genome constellation G9‐P[23]‐I1‐R1‐C1‐M1‐A8‐N1‐T1‐E1‐H1. All the genomic segments of three porcine G9 RVAs were closely related to those of porcine and/or porcine‐like human RVAs, demonstrating that the three viruses were porcine–human reassortant strains. To study the immunogenicity of the porcine G9 RVAs, 6‐week‐old female BALB/c mice were immunized with inactivated vaccines derived from porcine RVAs and then mated. The highest titres of neutralizing antibodies against G9P[23] and G9P[13] porcine RVAs (1, 291 ± 35.22 and 1:232 ± 39.28 respectively) were produced in mice 7 days after the second immunization. Suckling mice born to the vaccinated dams were protected by maternal antibodies against challenge with homologous strains. Overall, our data demonstrate the occurrence of porcine–human reassortants of G9 RVAs, and extend our understanding of the immunogenicity of porcine G9 rotaviruses. They also provide a basis for the development of a porcine G9 RVA vaccine.